Faktor-Faktor yang Memengaruhi Keberhasilan Usaha Slondok di Kalurahan Banjaroyo, Kapanewon Kalibawang, Kabupaten Kulon Progo - Syaidatul Mukharomah; Ina Fitria Ismarlin; Mastur Mastur (Universitas Sebelas Maret, 2025)
Cassava is a plant that is easy to grow, offering high potential for development as an alternative food ingredient. Business success is the success of a business actor in achieving their goals. This study aims to determine the impact of raw material quality, farming experience, infrastructure, business competition, and market access on the success of the slondok business in Banjaroyo Village. This study employs a quantitative approach using a questionnaire as the primary data collection instrument, conducted from November 2024 to February 2025 in Banjaroyo Village, Kalibawang Sub-district, Kulon Progo Regency. The respondents in this study consisted of 38 slondok business actors, selected using a saturated sample technique. The data analysis technique used in this study is multiple linear regression analysis, conducted using SPSS version 25.0. The results show that the variables of raw material quality (X1), farming experience (X2), facilities and infrastructure (X3), business competition (X4), and market access (X5) have a significant effect simultaneously (together) on the business success with a significance level of 0.018. Partially, raw material quality and farming experience have an effect on business success with a significance value of 0.007 and 0.045, respectively, while facilities and infrastructure, business competition, and market access do not have a significant effect. So, it is necessary to analyze other factors that support the success of the business run by slondok entrepreneurs.